Pulmonary histopathology in fatal paraquat poisoning - Senthil Kumar (University of São Paulo, 2021)
Paraquat is a potent herbicide widely used in the Indian agriculture industry. Human fatality due to paraquat poisoning is not uncommon in this country. The primary effect of paraquat is on the lungs, and the resultant pulmonary damage leads to the patient’s demise. There is a high mortality rate in paraquat poisoning as the treatment is usually supportive with no known antidote. There are limited human studies that have observed the histopathological changes in lungs in paraquat poisoning. The authors have discussed the time-related histopathological changes in lungs in paraquat poisoning on autopsy subjects. The role of anticoagulants and fibrinolytic agents in the treatment of this poisoning has also been discussed.